Induction Welding Technology for Thick Composites - Erartsin, O.; Sijmons, K.J.H.; Sterk, S.; Drent, R.A.; Bruin, A. de; Wirtz, T. (SAMPE, 2025)
Induction welding offers significant benefits for joining thermoplastic composites. Although it is commonplace to weld thin composites, welding thick composites remains a challenge due to the low magnetic field strength at the weld interface and overheating of the substrate closer to the coil. This study aims to develop an induction welding methodology based on KVE INDUCT® for thick composite substrates up to 8 mm thickness each, and demonstrate it for the first time. Quasi-isotropic C/LM-PAEK laminates were manufactured at thicknesses of approximately 4 mm and 8 mm. 4 mm + 8 mm and 8 mm + 8 mm substrates were welded from the thicker side. Several approaches were employed to weld the substrates: using a susceptor, adjusting the process parameters (weld speed & current), using additional heat sinks/constraints, and utilizing a magnetic flux concentrator. Welding thick composites required significantly lower speeds and higher currents compared to thin laminates. However, an innovative coil design involving a magnetic flux concentrator facilitated increasing the weld speed and lowering the current to values compared to standard thickness substrates (2.2 mm). Constraints placed along the edges of the substrates helped to constrain the flow by setting a physical boundary and extracting excess heat. Robust and high quality welds were realized with the innovative coil and additional heat sinks combined, demonstrated by C-scan analysis, without using a susceptor.